BIOEKONOMI IKAN TUNA SIRIP KUNING (Thunnus albacares) DARI LAUT BANDA - Imanuel Villian Trayanta Soukotta; Yofita Anaktototy; Janer Sangaji; Valentine Saleky (Universitas Pattimura, 2026)
Yellowfin tuna stocks in Maluku waters have enormous potential. The catch per unit effort affects production in terms of kilograms to tons, depending on the size of the fish caught. The rate of exploitation of yellowfin tuna fisheries is greatly influenced by vessel activity and trips at sea; the higher the catch activity, the lower the CPUE value during the fishing operation. The objective of this study is to analyze the bioeconomics of yellowfin tuna fisheries in the Banda Sea. The research methods used are financial analysis and production surplus modeling. The results of the study show that the financial analysis operating profit is IDR 1,165,674,612,500; Net profit is Rp. 1,165,619,566,920 with a profit rate of 1.25% and a benefit cost ratio of 2.25; profitability is 69157; the break-even point is Rp. 111,780,032; the payback period is 2 months, which is feasible. The Schaefer model produced a regression analysis between CPUE and trips, yielding a value of α = 508.3 and a value of b = -0.0856, MSY Copt of 754,389 tons, and Eopt of 2,968 trips. In fact, the number of vessels at the research location is more than 15 vessels, which can be regulated so that the number of vessel trips and the number of vessels can be reduced to prevent the tuna stock population from being exploited to extinction.